Strong dielectric-elastomer grippers with tension arch flexures - Heng, Kim-Rui (2019)
Soft grippers based on dielectric elastomer actuator (DEA) are usually too flimsy to perform the task of pick and place on a heavier object given their low payload capacity. This work developed a new design of DEA unimorph consists of a flexible frame holding at a DEA on the discrete support by a stiffer spine-like flexure of 380μm thick Polyvinyl chloride (PVC) sheet. It finds an equilibrium of curling up when the DEA's pre-stretch is partially released; it can electrically unfolds upon a voltage application. This dielectric elastomer unimorph of 3 grams produced a maximum voltage induced bending of close to 90° and a maximum voltage-induced blocked force of up to 168mN. Given their higher stiffness and large actuation, these 3-D shaped and strengthened DEA unimorphs can make stronger grippers for passive grasping and active pinching.